SAT 2014 : strategies, practice, and review - Kaplan Test Prep and Admissions (New York : Kaplan Pub., 2013)
A preparation guide for the SAT that provides subject reviews, four full-length practice tests with detailed answer explanations, test-taking strategies, and other resources.
Young Adult.
Young Adult
Keywords: SAT (Educational test); Universities and colleges -- Entrance examinations -- Study guides; Colleges and universities -- Entrance examinations -- Study guides; SAT (Educational test)